Evaluasi Kinerja Struktur Gedung Bertingkat Akibat Beban Gempa dengan Metode Pushover (Studi Kasus: Gedung Presisi 3 Mabes Polri) - Hilda Febriyani Pratiwi; Istiqomah Istiqomah; Ben Novarro Batubara (Portal: Jurnal Teknik Sipil, 2025)
Indonesia is located in the ring of fire and at the convergence of three tectonic plates, making it highly prone to earthquakes. This study aims to evaluate the seismic performance of the Presisi 3 Building at the Indonesian National Police Headquarters and determine its performance level based on displacement. The analysis was carried out using the response spectrum, equivalent static, and pushover methods with ETABS 18.1. The results indicate variations in maximum displacement and drift across the three methods. The pushover analysis produced a performance point with a base shear of 56,270.2575 kN and displacement of 461.685 mm in the x-direction, as well as a base shear of 49,926.4545 kN and displacement of 565.955 mm in the y-direction. According to ATC-40 and FEMA-440, the building’s performance level is categorized as Immediate Occupancy (IO), indicating that the structure remains safe and functional after an earthquake.Keywords: Displacement, Equivalent Static, Inter-story Drift, Pushover, Response Spectrum.